Augmented reality laboratory: Improving students’ interest in social science learning - Bashith, Abdul; Amin, Saiful; Firmantika, Lusty; Kurniawan, Muchammad Akbar; Idris, Idris (Edelweiss Applied Science and Technology, 2025)
The Augmented Reality (AR)-based social studies laboratory is a vital tool for improving learning, especially in training and practical environments, to aid students. This study focuses on: (1) creating an AR-based social studies laboratory product; (2) evaluating the feasibility of the developed AR-based social studies laboratory product; and (3) assessing the influence of the AR-based social studies laboratory product on students' learning interest. The research adopts a Research and Development (R&D) methodology, using the Borg & Gall development model. A one-group pretest-posttest design is employed to gauge the effect of the AR-based social studies laboratory on learning interest. The product was tested with students and lecturers from the Social Studies Education program at three Islamic state universities in Indonesia. The results indicate that: (1) the AR-based social studies laboratory was developed through an 8-stage process using the Borg & Gall model; (2) the AR-based social studies laboratory is both feasible and effective for educational purposes; and (3) the AR-based social studies laboratory significantly boosts students' learning interest. Future researchers are encouraged to expand on this study by exploring additional materials or topics not covered here, such as developing virtual reality (VR) applications, to further improve the learning experience.